Frequency Of Different Types Of Renal Stones By Composition In Patients Reported At Tertiary Care Hospital. - Muhammad Ali Suhail’, Nasrullah Aamer2, Mumtaz ali chandio’, Bhagwani , Aijaz Hussain Memon’, Mujeeburehman Sahito’,Ashok Kumar Lohano7 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Background: Renal stones are global health concern all over the world. Objectives: Analyze and checking frequency of renal stones by composition Design: cross sectional. Sample size: 355 Setting: People’s medical university hospital Nawabshah. Duration: January 2017 to January 2019. Methodology: All male and female patients with history of renal stones confirmed by ultrasound, x-ray KUB and followed by stone passing by medical and removal by surgical interventions. After receiving stone sample it was sent to laboratory for composition analyses. Results: Regarding the assessment of different type of renal stones, calcium oxalate was 102(26.59c), uric acid stone 1 25(32.59c), oxalate stone l 23(31.99c), phosphate .stones 29(7.59c), magnesium stones 01(0.39c), ammonium stone 01(0.3’fo), struvate stone 01(0.3ho), aspirate stone 01(0.3ho) and cystine stone 05(0.59c). Conclusions: present study concluded that uric acid stone, oxalate, calcium oxalate and phosphate stone were common in our setup